Արդի հայերենի թերի նախադասությունների մի դրսևորման մասին - Սոնա Նազարեթյան (ՀՀ ԳԱԱ հրատ.)
Неполные предложения формируются при полном или частичном опущении члена предложения. Частично опускаются (эллиптируются) и главные, и второстепенные члены предложения, наиболее часто–сказуемое, если оно выражается аналитической словоформой, или если оно составное сказуемое. The incomplete sentences emerge both through complete or partial contraction of a member of the sentence. Both the primary and secondary members of sentences may undergo partial omission or contraction. Predicates undergo contraction much more frequently. Predicate is much more likely to be omitted if it contains an analytical component or due to its compound character.
Keywords: Philology; Linguistics; Language and Literature